Pedophilia: A Quranic Wises to Parents from al-Ghazzālī (d. 1111) and ‘Ulwān (d. 1987) Remarks - Abur Hamdi Usman; Azwar Azwar; Muhammad Fakhrur Razi Shahabudin (International Journal of Islamic Khazanah, 2024)
Pedophilia is categorized as a mental problem caused by sexual orientation towards children. Therefore, Muslims need to be more vigilant and prepared for various social issues plaguing the world. At the same time, parents need to realize they have a big enough responsibility to ensure that children are not trapped or even victims of pedophile heinous acts. In this regard, this article analyzes several verses of the Quran, such as alTaḥrīm [66] verse 6 on role of parents, and Luqmān [31] verse 13 and Ṭaha [20] verse 132 regarding education of faith and wordship, and al-Isrā’ [17] verse 32 and al-Nūr [24] verse 30 about avoid adultery. These verses explicitly command Muslims to guard themselves and their families from the vices of pedophilia. Using a qualitative method, this study found the Quranic wises that sexual misconduct against minors such as pedophilia is an illegal and grave sin analogized through the premise of adultery, incest, and homosexuality. Therefore, every parent must fight hard to get stuck, let alone protect the perpetrators of this inverse disease. Parental awareness of the Quranic advice shared in this article is a gauge of the level of success against pedophilia.